ORGANIC PLANT PRODUCTS ARE OF MORE IMPROVED CHEMICAL COMPOSITION THAN CONVENTIONAL ONES - Golijan, Jelena; Sečanski, Mile (Food and Feed Research, 2021)
Considering the negative effects of conventional agricultural production, organic food production is a sustainable approach to production, which preserves the environment and protects human health. Organic products are products of high quality, without residues of pesticides and other harmful chemicals. Through the review of literature data, the authors of this paper presented a comparative study on the chemical compositions of organically vs. conventionally grown plants and their products. Dry matter, nitrates, sugars, vitamins, macro-and microelements, as well as, secondary metabolites have been singled out. The analysis of collected data revealed that organic products contained more dry matter, significantly fewer nitrates, fewer proteins and a higher proportion of amino acids, more sugars, vitamin C, numerous macro-and microelements (particularly Fe, Mg and P), more polyphenols and they had higher total antioxidant capacity than conventional products. Although many authors have been dealing for many years with the comparison of the nutritional composition of organic and conventional food products, a clear consensus whether organic products have an improved chemical composition compared to conventional products has not been reached yet, i.e. the conclusions are ambivalent. Therefore, further long-term studies are necessary to clarify the existing doubts.